2021
DOI: 10.3389/fgene.2021.647946
|View full text |Cite
|
Sign up to set email alerts
|

Brain Magnetic Resonance Imaging Phenome-Wide Association Study With Metal Transporter Gene SLC39A8

Abstract: The SLC39A8 gene encodes a divalent metal transporter, ZIP8. SLC39A8 is associated with pleiotropic effects across multiple tissues, including the brain. We determine the different brain magnetic resonance imaging (MRI) phenotypes associated with SLC39A8. We used a phenome-wide association study approach followed by joint and conditional association analysis. Using the summary statistics datasets from a brain MRI genome-wide association study on adult United Kingdom (UK) Biobank participants, we systematically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 63 publications
(109 reference statements)
1
8
0
Order By: Relevance
“…These results have been confirmed by work from Dickinson and colleagues, who showed that ZIP8 homozygous KO embryos have heart morphologic defects at embryonic day 14.5 [217]. Furthermore, and consistent with its detection throughout the CNS, SLC39A8 SNPs and mutations have been associated with specific brain structure alteration phenotypes by MRI [397,398]. Interestingly, over the past decade, SLC39A8 polymorphisms have been largely shown to be associated with higher schizophrenia risk [399][400][401][402][403][404].…”
Section: Zip8 (Slc39a8)mentioning
confidence: 52%
See 1 more Smart Citation
“…These results have been confirmed by work from Dickinson and colleagues, who showed that ZIP8 homozygous KO embryos have heart morphologic defects at embryonic day 14.5 [217]. Furthermore, and consistent with its detection throughout the CNS, SLC39A8 SNPs and mutations have been associated with specific brain structure alteration phenotypes by MRI [397,398]. Interestingly, over the past decade, SLC39A8 polymorphisms have been largely shown to be associated with higher schizophrenia risk [399][400][401][402][403][404].…”
Section: Zip8 (Slc39a8)mentioning
confidence: 52%
“…Mutations in SLC39A8 are also associated with congenital disorder of glycosylation, type IIn [218,219], in which patients display normal localization of the mutant ZIP8 protein, but exhibit low blood Zn and Mn levels as well as high levels of these cations in urine, suggesting renal wasting of the cations. SLC39A8 is also expressed in the brain, and SLC39A8 SNPs and mutations have been associated with specific brain structure alteration phenotypes by MRI [397,398]; SLC39A8 polymorphisms have also been shown to be associated with higher schizophrenia risk [399][400][401][402][403][404]. Thus, the phenotypes associated with mutations in SLC39A8 are complex and will require additional study.…”
Section: Discussionmentioning
confidence: 99%
“…rs13107325 is a highly pleiotropic missense variant that showed strong association with many complex human traits and diseases, including schizophrenia [ 5 , 15 ], blood lipids [ 36 , 55 ], steatohepatitis [ 56 ], intelligence [ 57 ], Crohn’s disease [ 58 ], severe idiopathic scoliosis [ 59 ], brain structure [ 60 62 ], and others. The risk allele of rs13107325 only appears in European (8%) and American (5%) populations, but not in Asian and African populations (Supplementary Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The SLC39A8 rs13107325 variant is one of the most pleiotropic polymorphisms known so far and has been repeatedly associated with neurological and metabolic disorders [ 45 , 46 ]. Interestingly, SLC39A8 polymorphisms, including rs13107325, and polymorphisms in linkage disequilibrium with rs13107325, are associated with different magnetic resonance imaging phenotypes of the brain [ 47 ].…”
Section: Genetics For Manganese Susceptibilitymentioning
confidence: 99%